2018
DOI: 10.1038/s41598-018-31098-x
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis of cell wall peptidoglycan amidation by the GatD/MurT complex of Staphylococcus aureus

Abstract: The peptidoglycan of Staphylococcus aureus is highly amidated. Amidation of α-D-isoglutamic acid in position 2 of the stem peptide plays a decisive role in the polymerization of cell wall building blocks. S. aureus mutants with a reduced degree of amidation are less viable and show increased susceptibility to methicillin, indicating that targeting the amidation reaction could be a useful strategy to combat this pathogen. The enzyme complex that catalyzes the formation of α-D-isoglutamine in the Lipid II stem p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
(88 reference statements)
1
14
0
Order By: Relevance
“…Using two complementary approaches, the in vitro pulldown assay and the in vivo interaction assay, we established that DUF1727 is responsible for the interaction between the two proteins MurT and GatD and for complex formation. This observation was confirmed by recent crystallographic structures, where GatD docks to the C terminus of MurT (20,21). Our results, obtained using distinct approaches, showed that DUF1727 is sufficient for the interaction with GatD and, more importantly, is essential for complex activity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Using two complementary approaches, the in vitro pulldown assay and the in vivo interaction assay, we established that DUF1727 is responsible for the interaction between the two proteins MurT and GatD and for complex formation. This observation was confirmed by recent crystallographic structures, where GatD docks to the C terminus of MurT (20,21). Our results, obtained using distinct approaches, showed that DUF1727 is sufficient for the interaction with GatD and, more importantly, is essential for complex activity.…”
Section: Discussionsupporting
confidence: 88%
“…The recently published structures of the MurT-GatD complexes from S. pneumoniae and S. aureus revealed a unique role for the C-terminal domain of MurT (DUF1727). Residue D349 plays a pivotal role in glutaminase activity by completing the catalytic triad (21). Our MurT-D349A mutation was responsible for a loss of complex formation and was not able to complement the amidation phenotype, which we attribute to the loss of protein stability and, consequently, its function (Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…2018; Noldeke et al . 2018). While GatD is inactive in the absence of MurT, the latter can functionally substitute the role of MurE (Munch et al .…”
Section: Introductionmentioning
confidence: 99%
“…The peptide moiety in the lipid II undergoes secondary modifications prior to the polymerization reactions such as amidation, the addition of extra amino acids, and esterification, etc. Recently, the crystal structure of an enzyme, GatD/MurT complex from S. aureus was solved at high resolution [2]. Amidation of the α-carboxyl group of the D-isoglutamate residue in Lipid II results in the formation of D-isoglutamine [3].…”
Section: Introductionmentioning
confidence: 99%